Infantile Nephropathic Cystinosis in Sulaimani Pediatric Teaching Hospital: A Retrospective Cohort Study - Hussein, Hunar Jamal; Hama Salih, Khalid; Mohammed Hasan, Adnan (Kurdistan Journal of Applied Research, 2018)
Cystinosis is a rare metabolic autosomal recessive disorder which characterized by intralysosomal accumulation of cystine. There are three forms; infantile nephropathic is the commonest forms. to evaluate clinical presentations and outcome of infantile cystinosis. A retrospective cohort study conducted in Sulaimani Pediatric Teaching Hospital on 25 patients with infantile cystinosis during May 1, 2014, to June 1, 2017. This study has depended on clinical symptoms and signs, and corneal crystallization for the diagnosis of cystinosis. Gender of the patients was 13 (52%) females and 12 (48%) males. The ages were ranged between (1-12 years) with a mean age of (6.25 years). Eight (32%) patients were from Sulaimani city, but the other 17 (68%) patients were from outside of Sulaimani. Moreover, a 17 (68%) of them were Arabic and the other eight (32%) were Kurdish ethnic groups. The study showed a 20 (80%) positive consanguinity with 19 (76%) positive family history of infantile cystinosis. Additionally, the age of first presentations was between (0.25-2 years) with a mean of (0.8 years). Clinical features included a 100% for polyuria, polydipsia, and failure to thrive. Furthermore, 10 (40%) presented with constipation, 23 (92%) photophobia and 5 (20%) blond hair. Complications included 24 (96%) rickets, 14 (56%) renal insufficiency, 5 (20%) hypothyroidism, 4 (16%) genu valgum, 3 (12%) growth hormone deficiency, and 3 (12%) developed end-stage renal disease. Subsequently, two patients died (8%) due to end-stage renal disease. Finally, there was a statistically significant relationship between both renal insufficiency (P-value = 0.042) and hypothyroidism (P-value < 0.001) with Kurdish ethnicity. Conclusion: Incidence of cystinosis was high among consanguineous parents and those patients who had a positive family history of cystinosis. Furthermore, the delay in diagnosis was due to atypical presentations and unavailability of specific investigations.